“A living lab within a lab”: approaches and challenges for scaling digital public health in resource-constrained settings - Mukherjee, Arunima S.; Sahay, Sundeep; Kumar, Rajesh; Banta, Rashi; Joshi, Neha (Frontiers in Public Health, 2023)
A living lab is an emerging concept, particularly in Europe, as a vehicle to develop digital innovations through a process of co-produced design and development which takes place, physically and socially, in real-life use contexts. However, there is limited research relating to guide our understanding of the process by which such labs are established, and digital innovations created. A particular research lack concerns the process by which these living labs can be scaled from where the innovation is developed to other settings which also require similar solutions. Furthermore, beyond Europe, the concept of a living lab has not found widespread application in low- and middle-income countries, particularly in their public health contexts. As public health systems offer the unique scaling challenge of “all or nothing”, implying that data is required from the whole population rather than isolated pilot settings. This promises rich potential to strengthen public systems but comes twin interconnected challenges. Firstly, building appropriate digital solutions to address local public health challenges, and secondly, in scaling them to other public health facilities. This paper investigates these twin challenges through ongoing empirical work in India. They identify three key areas of challenges and approaches to address these twin questions. The first concerns the establishing of an enabling governance structure of a “living lab within a lab”. The second concerns leveraging on the capabilities offered by free and opensource digital technologies. The third concerns the driving impetus to scaling through agile and co-constructed technical support.